2002
DOI: 10.1210/jcem.87.1.8142
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Autocrine Loop Involving IGF-II and the Insulin Receptor Isoform-A Stimulates Growth of Thyroid Cancer

Abstract: The insulin receptor (IR) occurs in two isoforms (IR-A and IR-B) resulting from alternative splicing of exon 11 of the gene. The IR-A isoform is predominantly expressed in fetal tissues and malignant cells and binds IGF-II with high affinity. We previously observed that IRs are overexpressed in thyroid cancer cells; now we evaluated whether these cells preferentially express IR-A and produce IGF-II, which would activate a growth-promoting autocrine loop. The IR content ranged 6.0-52.6 ng/100 microg cell membra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
81
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 189 publications
(89 citation statements)
references
References 37 publications
7
81
0
Order By: Relevance
“…These findings in myosarcoma cells follow the observation that IR-A is overexpressed in most human carcinomas Sciacca et al, 1999;Vella et al, 2002). In the thyroid model, the relative abundance of IR-A progressively increases from normal thyrocytes (that predominantly express IR isoform B) to differentiated papillary thyroid cancer cells and then to undifferentiated thyroid cancer cells that express a very high proportion (over 70%) of IR-A (Vella et al, 2002).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…These findings in myosarcoma cells follow the observation that IR-A is overexpressed in most human carcinomas Sciacca et al, 1999;Vella et al, 2002). In the thyroid model, the relative abundance of IR-A progressively increases from normal thyrocytes (that predominantly express IR isoform B) to differentiated papillary thyroid cancer cells and then to undifferentiated thyroid cancer cells that express a very high proportion (over 70%) of IR-A (Vella et al, 2002).…”
Section: Discussionsupporting
confidence: 80%
“…IR-B, in contrast, is predominantly expressed in normal adult tissues, but not in a variety of epithelial human malignancies (including cancers of the colon, lung, breast and thyroid), where IR-A expression predominates and may potentiate the biological effects of autocrine/paracrine production of IGF-II . In thyroid cancer, both the IGF-II autocrine production and the relative abundance of IR-A progressively increase with tumor de-differentiation, underscoring the possible relevance of this autocrine loop in tumor progression (Vella et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, many cancers are mitogenically responsive to insulin [16] and many cancer cell lines express insulin receptors [18,19]. Therefore high endogenous insulin levels and/or administration of exogenous insulin could theoretically have an adverse effect on neoplastic disease.…”
Section: Experimental Datamentioning
confidence: 99%
“…This suggests that the activity of the InsR-A may be promoted in an autocrine fashion, a concept confirmed by our findings that not only insulin but also IGF-II, significantly induced cell proliferation and conversely, substantial growth inhibition was seen after challenge with the IGF-1R/InsR inhibitor ABDP. Indeed, differential expression of the InsR-A by cancer cells compared to their normal counterparts has been reported in colon, lung, breast and thyroid cancer clinical samples (Vella et al, 2002) and additionally, these cancer types frequently overexpress IGF-II (Quinn et al, 1996;Renehan et al, 2000). In addition, other studies have shown that whereas IGF-II mainly induces mitogenesis after activating the InsR-A, insulin can also promote cell proliferation after binding to the InsR-A, as well as being able to drive metabolic events via this InsR isoform .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, stimulation of the InsR-A by insulin and IGF-II can promote cancer cell mitogenesis and survival (reviewed by Denley et al, 2003). In addition, several clinical cancer types including CRC, have been shown to preferentially express InsR-A Vella et al, 2002).…”
mentioning
confidence: 99%